Boganmeldelser - Peter Gottlieb; H. Kallehauge; Gorm Toftegaard Nielsen; Beth Grothe Nielsen; Peter Garde; Eric Bo Ebskov; Kåre Bødal; J. Heilbo; Vagn Greve; Nell Rasmussen; Ragnar Hauge; Inkeri Anttila; et al. (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews